Complex Near‐Surface Rheology Inferred From the Response of Greater Tokyo to Strong Ground Motions. Issue 7 (13th July 2018) - Viens, Loïc; Denolle, Marine A.; Hirata, Naoshi; Nakagawa, Shigeki
Abstract: Strong ground motion can induce dynamic strains large enough for the Earth's subsurface to respond nonlinearly and to cause permanent, or plastic, damage. The 2011 M w 9.0 Tohoku‐Oki earthquake, Japan, generated exceptional and well‐recorded ground motions in the greater Tokyo area. We use continuous records from 234 stations of the dense MeSO‐net seismic network to monitor the temporal evolution of the material properties of the shallow subsurface (upper ∼100 m). We apply the single‐station cross‐correlation method to reconstruct the near‐surface reflectivity response through time. We find that the strong ground motions from the mainshock caused large perturbations in the near‐surface structure, with significant drops in seismic velocities up to 11%. For most sites, we observe a logarithmic and complete recovery of the seismic wave speed, suggesting a relaxation process that can be explained by a viscoelastic rheology. Some sites exhibit an instantaneous and permanent change, which suggests a plastic rheology. Finally, dense seismic measurements allow for statistical inference between seismic velocity drops, recovery time scales, and permanent perturbations and ground motion strength and site conditions. This study highlights the potential for seismic interferometry to assess near‐surface rheology with dense seismic arrays. Plain Language Summary: Strong ground motions from earthquakes can significantly modify the physical properties of the Earth's near surface. A large range of effects has been observed during past earthquakes, from softening of the medium to, in extreme cases, its liquefaction. As these changes in the near surface can threaten the safety of human‐made constructions, monitoring and understanding their temporal evolution during and after an earthquake is critical. We use an approach that only requires one seismic sensor to monitor the temporal evolution of the near‐surface properties. We apply this technique to a dense seismic array deployed in the greater Tokyo area, which experienced strong ground shaking during the 2011 M w 9.0 Tohoku‐Oki earthquake. The strong ground motions caused small‐to‐large drops of the near‐surface rigidity over the greater Tokyo area, followed by a relaxation process over different timescales. The response of the near surface is impacted by both preearthquake site conditions and the strength of ground motions of the 2011 M w 9.0 Tohoku‐Oki earthquake. Key Points: Seismic interferometry is used to monitor the response of the near surface to strong ground motions Seismic velocity changes up to 11% occurred in greater Tokyo during the 2011 M w 9.0 Tohoku‐Oki event Changes in the near surface correlate with site conditions and ground motion strength